2009
DOI: 10.1590/s0370-44672009000300017
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização microestrutural dos alumínios comerciais AA1100, AA1050 e AA1070 e do alumínio superpuro AA1199

Abstract: Foi realizado um estudo comparativo entre três alumínios de pureza comercial com diferentes níveis de pureza - AA1100 (99,00%), AA1050 (99,50%) e AA1070 (99,70%), produzidos em escala industrial pelo processo semicontínuo ou Direct Chill (DC) - e o alumínio superpuro, AA1199 (99,995%), produzido em laboratório. Foram utilizadas várias técnicas de análise microestrutural: microscopia óptica convencional, microscopia eletrônica de varredura, microscopia óptica com luz polarizada, medidas de condutividade elétric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, the electrical conductivity values for the high purity aluminum AA1199 (Table 2) and the AA1050 aluminum are higher than those measured for the AA4006 alloy. Therefore, it may be observed that the electrical conductivity decreases with the increase in the total quantity of solute, following the decreasing order: AA1199 > AA1050 DC ≈ AA1050 TRC > AA4006 DC ≈ AA4006 TRC (Oliveira and Padilha, 2009;Souza et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the electrical conductivity values for the high purity aluminum AA1199 (Table 2) and the AA1050 aluminum are higher than those measured for the AA4006 alloy. Therefore, it may be observed that the electrical conductivity decreases with the increase in the total quantity of solute, following the decreasing order: AA1199 > AA1050 DC ≈ AA1050 TRC > AA4006 DC ≈ AA4006 TRC (Oliveira and Padilha, 2009;Souza et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity measurements can be used for the evaluation of the concentration of solute atoms in the solid solution of aluminum alloys, since this property decreases with increase of the solute content in these alloys (Oliveira and Padilha, 2009). In this way, heat treatments, which alter the solute concentration in solid solution, strongly influence the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since, the SS tool material shows good attraction between the metallic molecules attributing of smooth flow of current at machining zone. At the same time, AMC tool have lesser intermolecular metallic bonding among the molecules [21].Hence the uniform current flow in the IEG increases the MR in the SS tool than AMC tool. The SS tool produces around 71.6 % higher MR than AMC tool for the parameter combination of 8V, 85% and 23 g/l.…”
Section: Influences Of Machining Voltage On Oc and Mrmentioning
confidence: 96%